THE PROMOTIONAL CONTENT STRATEGY ON THE @SCREENPLAYFILM INSTAGRAM ACCOUNT TO BOOST THE APPEAL OF THE FILM PERTARUHAN SEASON 3 - Aji Bagus Prasetyo; RR Roosita Cindrakasih (Yayasan Azam Kemajuan Rantau Anak Bengkalis, 2026)
This study aims to analyze the content promotion strategy on the Instagram account @screenplayfilm in increasing the audience appeal of Pertaruhan The Series Season 3. This research uses qualitative methods with a descriptive and case study approach. Data was obtained through observation, in-depth interviews with informants directly involved in the promotion process, and documentation of Instagram content. The analysis was conducted using the AIDA model (Attention, Interest, Desire, Action). The results show that the @screenplayfilm account implements a systematic content strategy through various types of content including teasers, trailers, reels, behind the scenes, and the use of interactive Instagram features. This strategy successfully fulfills all stages of AIDA: attracting attention through strong visuals, building interest through storytelling and actor popularity, cultivating desire through story clips that provoke curiosity, and encouraging action through active engagement in the form of likes, comments, shares, and views. This study concludes that Instagram-based content promotion strategies are proven effective in increasing audience appeal for Indonesian local series.